Using NLP Python Tools in Methods of Content Analysis - Razno, Maria; Khairova, Nina (My University, 2020)
This article describes the relevance of the content analysis task applied on Twitter text data using various NLP methods, that can be implemented on Python programming language. It also includes the concept of different NLP methods and algorithms, its main varieties and the most popular Python packages and libraries for working with text data. The content analysis algorithms based on the text processing is introduced in this study. It shows how to use NLP methods in practice.
Keywords: content analysis; Python; text classification; text processing NLP; NLTK; Twitter